Socio-economic impact of agro-tourism development on local residents case study : Sungai Galah, Tanjung Tualang, Perak / Nur Shahida Hamidi and Siti Fairuz Che Pin - Hamidi, Nur Shahida; Che Pin, Siti Fairuz (2019)
Agro-tourism is a tourism concept that is rapidly gaining popularity in Malaysia as it offers tourists an assortment of activities relating to the agriculture sector. Perak Agro-tourism Resort (PATRO) located at Sungai Galah, Tanjung Tualang has offered traditional environment vacation by having ecoadventures and agro-tourism activities. The aim of this study is to analyze how the socio-economic impacts of agrotourism development are perceived by the local residents. A questionnaire survey has been conducted among 52 respondents of local residents who reside in the area of Sungai Galah, Tanjung Tualang, Perak. The socioeconomic were analyzed based on four (4) main aspects, i.e. economic assessment, social assessment, cultural assessment, and environmental assessment. The findings reveal that the local residents were positively and also negatively affected by the agro-tourism activities and development in Sungai Galah. As an overall conclusion, assessment on economic, social, cultural and environment compliment the objective of this study. Proper planning and policies are the crucial part need to be taken by the industry player to ensure the natural attraction can be maintained besides enlivening the economic structure.